TRACING NATIVE TEACHER TALK AND CLASSROOM INTERACTION IN EFL CONTEXT - Jihan aisah kirahla; Peptia Asrining tyas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Since teacher talk is a necessary input for the students in an EFL (English as a Foreign Language) classroom, the objectives of this study are analyzing the categories of teacher talk and the classroom interaction in young learners’ classroom at reputable English Courses in Malang. This study used descriptive qualitative as the research design by using an observation sheets and an interview guide as the instruments. Besides, the researcher recorded the audio for every meeting. The result shows that, the teacher talk used in the classroom has been classified as direct teacher talk covering informing something, giving directions, and justifying students’ authority. For the classroom interaction in the class, it was found that the way students responded to their teacher’s talk was by individually. Further, it was found that direct teacher talk was implemented in the learning process and the implementations of this teacher talk were also connected with the way the students respond to their teacher talk